DNA binding and antiradical potential of ethyl pyruvate: Key to the DNA radioprotection. (1st December 2020) - Sharma, Deepti; Singh, Anju; Pathak, Mallika; Kaur, Lajpreet; Kumar, Vinod; Roy, Bal G.; Ojha, Himanshu
Abstract: DNA is the store house of all necessary hereditary information for growth of cells and tissues. Physiological functionality of DNA depends on its 3D helical structure and any distortion in a structure may lead to mutation and genomic instability that may translate into disease like cancer. In order to prevent DNA damage, an exogenous compound is required that can either scavenge the excess free radicals or enhance the structural integrity of DNA through binding. In the present study, the binding mechanism of ethyl pyruvate (EP) with DNA models using different spectroscopic techniques was investigated for their structural integrity. Besides, 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays were performed to determine the antioxidant scavenging of EP. Plasmid DNA relaxation assay was performed to assess the radioprotection efficacy of EP in the plasmid DNA. Circular dichroism (CD) and UV–Vis absorbance spectroscopic data confirmed the conformation change in ctDNA upon binding with EP. The molecular docking visualized that EP stacks between the DNA bases with a glide score of −2.117 k c a l m o l while EP binds in the minor groove region of DNA with the glide score of −1.414 k c a l m o l . DPPH and FRAP data confirmed that EP scavenges significantly radicals at higher concentrations. In vitro radioprotection study in plasmid DNA pBR322 showed that EP retained the supercoiled form of plasmid DNA at 50 Gy radiation dose. Graphical abstract: Image 1 Highlights: CD and UV–Vis spectra of ctDNA indicated conformational change after EP binding. Docking showed EP binds reversibly as an intercalator and in a minor groove of DNA. EP is an effective antioxidant. EP significantly protects DNA against γ-radiation induced damage.